Pengaruh Kompensasi terhadap Implementasi Entrepreneurial Government dan Kinerja Aparatur Sipil Negara pada Dinas Kehutanan Provinsi Jambi - Octora, Shinta; Lubis, Tona Aurora; Indrawijaya, Sigit (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effect of compensation on the implementation of the Entrepreneurial Government concept and the performance of State Civil Apparatus (SCA) at the Jambi Provincial Forestry Service. This study used a quantitative approach with a survey method. Primary data were obtained through questionnaires distributed to 74 respondents, consisting of SCA within the Jambi Provincial Forestry Service. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results indicate that compensation has a positive and significant effect on the implementation of Entrepreneurial Government and the performance of SCA. Furthermore, the implementation of Entrepreneurial Government has been shown to significantly improve the performance of SCA.